Etiological factors as predictor of rehabilitation in patients after carebrovascular insult - Edina Tanović; Damir Čelik (Journal of Health Sciences, 2012)
Introduction: Cerebrovascular insult (CVI) is acute or sub-acute occurrence of symptoms which signal death of cerebral cells caused by localized disruption of arterial circulation in the brain. The goal of this study is to investigate whether ischemic or hemorrhagic CVI can be used as predictor of rehabilitation. Methods: A retrospective study was conducted in the period from January 2009 to the December 2009 and as a source of data we used medical records. The study included 89 patients who had CVI and who were hospitalized at the Clinic for Physical medicine and rehabilitation, Clinical Center University of Sarajevo (CCUS). We analyzed socio-demographic variables such as gender and age and clinical variables: the diagnosis, the length of stay in hospital (LOH), and Barthel index (BI) at admission and discharge from hospital. Results: Out of 89 patients, 78/89 (87.6%) were patients with ischemic CVI (group A), and 11/89 (12.4%) with hemorrhagic CVI (group B). There was not a signifi cant association between the gender and type of CVI [(χ2(1)= .041, P> .05]. There was a statistically signifi cant difference in median of length of hospitalization (LOH) between two groups (U=186.5; z=-3,025; P= .002). There was not a statistically signifi cant difference in median of BI at admission (U=317.0; z=-1,399; P= .162) and  discharge (U=319.0; z=-1.374; P= .169) between two groups. Conclusion: Patients with hemorrhagic CVI have a longer stay in hospital and consequently more expensive cost of treatment.